2016
DOI: 10.5152/jtgga.2015.15174
|View full text |Cite
|
Sign up to set email alerts
|

Hypodontia and ovarian cancer: A systematic review

Abstract: Spanish were excluded from this review. The retrieved data from each of the included studies were focused on the publication type, the number of patients included in each study, the number of patients included in the control group, the incidence of hypodontia, the number of missing teeth, the type of missing teeth, the distribution of hypodontia, the presence of ovarian cancer in family medical history, and the presence of isolated genes correlated to ovarian cancer. ResultsThe performed search in PubMed and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In addition to family and association studies, epidemiological data on tooth agenesis and cancer were collected in five original articles 71‐75 (discussed below) and four reviews 76‐79 . However, these reviews are based only on epidemiological data of mentioned five sources.…”
Section: Tooth Agenesis As a Predictive Marker For Cancermentioning
confidence: 99%
“…In addition to family and association studies, epidemiological data on tooth agenesis and cancer were collected in five original articles 71‐75 (discussed below) and four reviews 76‐79 . However, these reviews are based only on epidemiological data of mentioned five sources.…”
Section: Tooth Agenesis As a Predictive Marker For Cancermentioning
confidence: 99%
“…1 The reported incidence of tooth agenesis is 3%-10% depending on the population being studied. [2][3][4] The incidence is higher in females, and 60% of individuals exhibit unilateral tooth agenesis. 3 Third molars are the most commonly missing permanent teeth; 23% is the often-cited incidence rate.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these data, from 2014 to September 2018, no new research publications confirmed the hypothesis of the coincidence of hypodontia and ovarian cancer. In 2016, a review paper by Iavazzo was published on the relationship between ovarian cancer and hypodontia; this qualified four publications for review [28], one of which was the publication of Fekonja et al from 2015, which is a description of a study whose results were published a year earlier [27,29], as can be seen from the location and year of the study, the size of the study and control group, and the frequency of hypodontia in both groups. This publication was therefore excluded from our review; it did, however, aim to compare data on the stage of advancement and the type of cancer in patients with and without hypodontia [29].…”
Section: Discussionmentioning
confidence: 99%